Controlabilidade, problema inverso, problema de contato e estabilidade para alguns sistemas hiperbólicos e parabólicos - Sousa Neto, Gilcenio Rodrigues de (2016)
In this thesis we study controllability results, asymptotic behavior and inverse problem related to some problems of the theory of partial di erential equations. Two particular systems are the focus of the study: the Mindin-Timoshenko system, describing the vibrational motion of a plate or a beam, and the phase eld system describing the temperature and phase of a medium having two distinct physical states. The rst chapter is devoted to the study of the 1-D Mindlin-Timoshenko system with discontinuous coe cient. A Carleman inequality is obtained under the assumption of monotonicity on the beam speed. Subsequently, two applications are provided: the controllability of the control system acting on the boundary and Lipschitzian stability of the inverse problem of recovering a potential from a single measurement of the solution. In the second chapter we consider a contact problem characterized by the behavior of a two-dimensional plate whose board makes contact with a rigid obstacle. The formulation of this problem is presented by the 2-D Mindlin-Timoshenko system with boundary conditions and suitable damping terms. Concerning such system, is proved via penalty techniques, the existence of solution and that the system energy has exponential decay when the time approaches in nity. In the third chapter, the study is aimed at a nonlinear phase- eld system de ned in a real open interval. Here we present some controllability results when a single control acts, by means of Dirichlet conditions, on the temperature equation of the system on one of the endpoints of the interval. To prove the results is used the method of moments, plus a spectral study of operators associated to the system and xed point theory to deal with the nonlinearity.